The impact of EU cartel policy reforms on the timing of settlements in private follow-on damages disputes: An empirical assessment of cases from 2001 to 2015 - Hans Friederiszick; Linda Gratz; Michael Rauber (European School of Management and Technology (ESMT), 2020)
Private cartel damages litigation is on the rise in Europe since early 2000. This development has been initiated by the European courts and was supported by various policy initiatives of the European Commission, which found its culmination in the implementation of the EU Directive on Antitrust Damages end of 2016. This paper explores the impact of this reform process on effective compensation of damaged parties of cartel infringements. For that purpose we analyse all European cartel cases with a decision date between 2001 and 2015, for which we analyse litigation activity and speed. Overall, we find a substantial reduction of the time until first settlement (increase in litigation speed) together with a persisting high share of cases being litigated (high litigation activity). This supports the view that the reform not only increased the claimant's expectation about the amount of damages being awarded, but also resulted in an alignment in the expectations of claimants and defendants in the final damages amount, i.e. the European Commission succeeded in reaching its objective to clarify and harmonize legal concepts across Europe.
urn:nbn:de:101:1-2020062515113092591136
Keywords: 650; cartels; private damages; competition law